Equation of state modeling of the phase equilibria of asymmetric CO 2 + n-alkane binary systems using mixing rules cubic with respect to mole fraction - Cismondi Duarte, Martín (2010)
Both the equation of state (EOS) and the quadratic mixing rules proposed by van der Waals towards the end of the XIX century were enormous contributions to the understanding and modeling of fluids phase behavior. They set the basis for a consistent and useful representation of phase equilibria for a great diversity of mixtures. Nevertheless, the models for representing phase equilibria and physico-chemical properties of asymmetric systems may require more flexible mixing rules than the classical quadratic van der Waals (vdW) mixing rules or their equivalent (with regard to the number of available interaction parameters) in modern equations of state. In particular, the phase equilibria of binary mixtures containing CO2 and heavy n-alkanes have been studied by an important number of authors and using different types of models, achieving only partially accurate results and realizing the difficulties that these systems showing type III phase behavior (from C14 on) present for predicting or even correlating their phase equilibrium data in wide ranges of temperature and pressure. Cubic mixing rules (CMRs), implemented as a natural extension of the classical quadratic mixing rules, constitute the simplest alternative among different flexible approaches. In addition, they have the advantage of allowing correlation of multicomponent data by fitting ternary interaction parameters, while leaving invariant the description of the constituent binary systems. In this work, and after having detected the need for temperature-dependent interaction parameters in a previous study, we implemented an automated parameterization procedure based on characteristic key-points for binary systems showing type III phase behavior. Using the RK-PR EoS coupled to CMRs we present the parameters obtained and results showing for the first time a quite successful complete description of asymmetric CO 2 + n-alkane binary systems, with n-alkane carbon number from 14 to 22. © 2010 Elsevier B.V. © 2010 Elsevier B.V. All rights reserved.